Development of versatile and potent monoquaternary reactivators of acetylcholinesterase - Gorecki, Lukas; Hepnarova, Vendula; Karasova, Jana Zdarova; Hrabinova, Martina; Courageux, Charlotte; Dias, José; Kucera, Tomas; Kobrlova, Tereza; Muckova, Lubica; Prchal, Lukas; Malinak, David; Jun, Daniel; et al. (Archives of toxicology, 2021)
To date, the only treatments developed for poisoning by organophosphorus compounds, the most toxic chemical weapons of mass destruction, have exhibited limited efficacy and versatility. The available causal antidotes are based on reactivation of the enzyme acetylcholinesterase (AChE), which is rapidly and pseudo-irreversibly inhibited by these agents. In this study, we developed a novel series of monoquaternary reactivators combining permanently charged moieties tethered to position 6- of 3-hydroxypyridine-2-aldoxime reactivating subunit. Highlighted representatives (21, 24, and 27; also coded as K1371, K1374, and K1375, respectively) that contained 1-phenylisoquinolinium, 7-amino-1-phenylisoquinolinium and 4-carbamoylpyridinium moieties as peripheral anionic site ligands, respectively, showed efficacy superior or comparable to that of the clinically used standards. More importantly, these reactivators exhibited wide-spectrum efficacy and were minutely investigated via determination of their reactivation kinetics in parallel with molecular dynamics simulations to study their mechanisms of reactivation of the tabun-inhibited AChE conjugate. To further confirm the potential applicability of these candidates, a mouse in vivo assay was conducted. While K1375 had the lowest acute toxicity and the most suitable pharmacokinetic profile, the oxime K1374 with delayed elimination half-life was the most effective in ameliorating the signs of tabun toxicity. Moreover, both in vitro and in vivo, the versatility of the agents was substantially superior to that of clinically used standards. Their high efficacy and broad-spectrum capability make K1374 and K1375 promising candidates that should be further investigated for their potential as nerve agents and insecticide antidotes.
Keywords: Male; simulace molekulární dynamiky; antidota; Structure-Activity Relationship; myši inbrední BALB C; Molecular Dynamics Simulation; Organophosphorus compounds; Oximes; mužské pohlaví; acetylcholinesterasa; Cholinesterase Reactivators; Mice, Inbred BALB C; vztahy mezi strukturou a aktivitou; Antidotes; Nerve agents; Animals; ženské pohlaví; Oxime reactivator; Butyrylcholinesterase; zvířata; reaktivátory cholinesterasy; myši; Insecticides; oximy; Mice; Female; Acetylcholinesterase; Organophosphates